'Accepting what is': an approach for managing the long-term sexual side effects of selective serotonin reuptake inhibitors (SSRIs) in women - O'Mullan, C.; Doherty-Poirier, Maryanne; Coates, R.; Tilley, P. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2015)
Sexual difficulties may not be a pressing issue for women on antidepressants during the early phase of selective serotonin reuptake inhibitor (SSRI) treatment; however, this can emerge as a substantial problem once women are stabilised on medication. Little is known about how women cope with the adverse sexual effects of SSRIs. This qualitative study used Interpretative Phenomenological Analysis to explore the experiences of Australian women currently coping with the sexual side effects of this antidepressant. Interviews were conducted with 10 heterosexual women, aged 45 years and younger. Four major coping strategies were identified “searching”, “suffering in silence”, “trying to resolve” and “accepting what is”. This paper explores one particular response “accepting what is”, which includes a number of strategies commonly employed by women on long-term medication. Findings from the study have particular relevance for sex and relationship therapists and may assist women in managing sexual side effects that are perceived to be beyond their control. This paper adds to the current literature by increasing understanding of how “accepting what is” can be a step forward, particularly for women who have chosen to remain on long-term medication. In theoretical terms, a deeper understanding of how women cope could inform debate about the appropriate management of long-term sexual side effects in the absence of effective pharmacological interventions.